Randomized Clinical Trial of Hydrocodone/Acetaminophen Versus Codeine/Acetaminophen in the Treatment of Acute Extremity Pain After Emergency Department Discharge. (March 2014) - Chang, Andrew K.; Bijur, Polly E.; Munjal, Kevin G.; John Gallagher, E.; Mycyk, Mark B.
Abstract Objectives The objective was to test the hypothesis that hydrocodone/acetaminophen (Vicodin [5/500]) provides more efficacious analgesia than codeine/acetaminophen (Tylenol #3 [30/300]) in patients discharged from the emergency department (ED). Both are currently Drug Enforcement Administration (DEA) Schedule III narcotics. Methods This was a prospective, randomized, double‐blind, clinical trial of patients with acute extremity pain who were discharged home from the ED, comparing a 3‐day supply of oral hydrocodone/acetaminophen (5 mg/500 mg) to oral codeine/acetaminophen (30 mg/300 mg). Pain was measured on a valid and reproducible verbal numeric rating scale (NRS) ranging from 0 to 10, and patients were contacted by telephone approximately 24 hours after being discharged. The primary outcome was the between‐group difference in improvement in pain at 2 hours following the most recent ingestion of the study drug, relative to the time of phone contact after ED discharge. Secondary outcomes compared side‐effect profiles and patient satisfaction. Results The median time from ED discharge to follow‐up was 26 hours (interquartile range [IQR] = 24 to 39 hours). The mean NRS pain score before the most recent dose of pain medication after ED discharge was 7.6 NRS units for both groups. The mean decrease in pain scores 2 hours after pain medications were taken were 3.9 NRS units in the hydrocodone/acetaminophen group versus 3.5 NRS units in the codeine/acetaminophen group, for a difference of 0.4 NRS units (95% confidence interval [CI] = –0.3 to 1.2 NRS units). No differences were found in side effects or patient satisfaction. Conclusions Both medications decreased NRS pain scores by approximately 50%. However, the oral hydrocodone/acetaminophen failed to provide clinically or statistically superior pain relief compared to oral codeine/acetaminophen when prescribed to patients discharged from the ED with acute extremity pain. Similarly, there were no clinically or statistically important differences in side‐effect profiles or patient satisfaction. If the DEA reclassifies hydrocodone as a Schedule II narcotic, as recently recommended by its advisory board, our data suggest that the codeine/acetaminophen may be a clinically reasonable Schedule III substitute for hydrocodone/acetaminophen at ED discharge. These findings should be regarded as tentative and require independent validation in similar and other acute pain models.